Causal effects on employment after first birth: A dynamic treatment approach - Bernd Fitzenberger; Katrin Sommerfeld; Susanne Steffes (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
The effects of childbirth on future labor market outcomes are a key issue for policy discussion. This paper implements a dynamic treatment approach to estimate the effect of having the first child now versus later on future employment for the case of Germany, a country with a long maternity leave coverage. Effect heterogeneity is assessed by estimating ex post outcome regressions. Based on SOEP data, we provide estimates at a monthly frequency. The results show that there are very strong negative employment effects after childbirth. Although the employment loss is reduced over the first five years following childbirth, it does not level off to zero. The employment loss is lower for mothers with a university degree. It is especially high for medium-skilled mothers with long prebirth employment experience. We find a significant reduction in the employment loss for more recent childbirths.
urn:nbn:de:bsz:180-madoc-352925
Keywords: C14; J13; J22; 330; Female labor supply; Maternity leave; Dynamic treatment effect; Inverse Probability Weighting